Optimum Condition for In Vitro Hatching of Freshwater Prawn, Macrobrachium rosenbergii Eggs - Farah Nur Wahyuni Zainuddin (2015)
Macrobrachium rosenbergii also known as giant freshwater prawn is the largest genus in family of Palaemonidae. It is commonly used in aquaculture industry. M.rosenbergii female will migrate from freshwater area to brackish water area to fertilize and release their eggs. They will incubate their eggs in the brood chamber for about 19-22 days. The aims of this study are to investigate the optimum condition for in vitro hatching of M. rosenbergii eggs and to observe the larval development of M. rosenbergii. The study is conducted in the laboratory with different temperature (25. 28 and 32°C) and salinity (3, 6 and 9 ppt). Then. the larval stage development for the larvae is monitored using microscope. The finding from this study shows that the optimum temperature and salinity for in vitro hatching is at 25°C and 6 ppt. While the optimum temperature and salinity of in vivo hatching are at 25-32°C and 3-9 ppt. Besides that. the changes in larvae stage is monitored until stage IV out of XI stage. In addition, the optimum conditions need to be maintaining for the larval development. The findings of this study are useful to increase production of freshwater prawn through in vitro eggs hatching potentially to be done in large scale that will help to fulfill the demand of M. rosenbergii in Malaysia.